A directly comparative two-gate case–control diagnostic accuracy study of the pure tone screen and HearCheck screener tests for identifying hearing impairment in school children. Issue 7 (11th July 2017) - Ukoumunne, Obioha C; Hyde, Chris; Ozolins, Mara; Zhelev, Zhivko; Errington, Sam; Taylor, Rod S; Benton, Claire; Moody, Joanne; Cocking, Laura; Watson, Julian; Fortnum, Heather
Abstract : Objectives: This study directly compared the accuracy of two audiometry-based tests for screening school children for hearing impairment: the currently used test, pure tone screen and a device newly applied to children, HearCheck Screener. Design: Two-gate case–control diagnostic test accuracy study. Setting and participants: Hearing impaired children ('intended cases') aged 4–6 years were recruited between February 2013 and August 2014 from collaborating audiology services. Children with no previously identified impairment ('intended controls') were recruited from Foundation and Year 1 of schools between February 2013 and June 2014 in central England. The reference standard was pure tone audiometry. Tests were administered at Nottingham Hearing Biomedical Research Unit or, for some intended cases only, in the participant's home. Main outcome measures: Sensitivity and specificity of the pure tone screen and HearCheck tests based on pure tone audiometry result as reference standard. Results: 315 children (630 ears) were recruited; 75 from audiology services and 240 from schools. Full test and reference standard data were obtained for 600 ears; 155 ears were classified as truly impaired and 445 as truly hearing based on the pure tone audiometry assessment. Sensitivity was estimated to be 94.2% (95% CI 89.0% to 97.0%) for pure tone screen and 89.0% (95% CI 82.9% to 93.1%) for HearCheck (difference=5.2% favouring pure tone screen; 95% CI 0.2% to 10.1%; p=0.02). Estimates for specificity were 82.2% (95% CI 77.7% to 86.0%) for pure tone screen and 86.5% (95% CI 82.5% to 89.8%) for HearCheck (difference=4.3% favouring HearCheck; 95% CI0.4% to 8.2%; p=0.02). Conclusion: Pure tone screen was better than HearCheck with respect to sensitivity but inferior with respect to specificity. As avoiding missed cases is arguably of greater importance for school entry screening, pure tone screen is probably preferable in this context. Study registration number: Current controlled trials: ISRCTN61668996 .